Social, Decolonial, and Transnational Museology. Reflections from the Global South, and some Current Brazilian Cases - Ruiz-Gómez, Lorea Ariadna (Brepols Publishers, 2025)
In this dissertation, we are going to approach Latin American social museology and we will deal with thee Brazilian case, focusing on the museum, and art system of Sao Paulo, since it is a neuralgic pole of global contemporaneity and regarding the revision of its museums from a decolonial, and territorial perspective

En esta aportación se aborda la museología social latinoamericana y concretamente el caso brasileño, centrándonos en el sistema museístico y artístico de Sao Paulo, por ser un polo neurálgico de la contemporaneidad global, así como en la revisión de sus museos, desde una perspectiva decolonial y territorial.
https://www.brepols.net/open-access/self-archiving-policy
Keywords: Museología; Museos - Brasil; Postcolonialismo; Museology; Decolonialism; Social museology; Brazilian museums; Ibero-american museology; Transnational museology; Integral museum; Art institutions